Authenticity in A Real Young Girl (Catherine Breillat, 1976). Issue 1 (October 2019) - Belot, Sophie
Abstract : In French cinema, representations of girls have often been associated with films made by women, as demonstrated by Carrie Tarr with Brigitte Rollet (2001). They claim that the young girl is the major cinematographic topic for a woman's first film, and names, such as Céline Sciamma in the late 2000s, Diane Kurys and Catherine Breillat in the 1970s, substantiate this position. However, Breillat's A Real Young Girl was different, as it attracted critics' acerbic reception and was subsequently banned for its open depiction of a young girl's sexual experiences. It is argued that Breillat's images of the young girl's sexual initiation in the 1970s brings to the fore the significance of the idea of authenticity in relation to sex and cinema. Examining the representation of the 'real young girl' highlights the ideas of reflexivity and creativity attached to the existentialist notion of authenticity. This article aims to show that the young girl stands as a metaphor for Breillat's auteurist approach to challenging existing filmic conventions.